Spectroscopic (IR and Raman) Analysis and Density Functional Theory (DFT) Investigation on Cyclohexanone Oxime - Sharma, Sagar; Khanal, Kamal (Annual Oxford Journal, 2025)
In this research, the molecular, electronic, and spectroscopic properties of cyclohexanone oxime were investigated using density functional theory (DFT) in both the gas phase and solvents (water, DMSO, and ethanol) at the B3LYP/6-311++G (d,p) level of theory. HOMO-LUMO energy calculations showed higher stability of cyclohexanone oxime in solvent phases than in the gas phase due to a larger energy gap in solvents (6.66 eV) compared to the gas phase (6.45 eV). Thermodynamic parameters, molecular electrostatic potential (MEP) maps, density of states (DOS) spectra, and Mulliken atomic charges were investigated to gain a broad understanding of the physicochemical behavior of the cyclohexanone oxime molecule. Further analysis included non-covalent interaction (NCI) and reduced density gradient (RDG) plots to understand weak interactions, and Fukui function calculations to identify different reactive sites in the cyclohexanone oxime molecule. Spectroscopic properties were studied by simulating FT-IR, FT-Raman, and UV-Vis spectra. All these parameters were then compared with all the available experimental results on the cyclohexanone oxime compound. These comprehensive theoretical investigations provided valuable information on the structural, electronic, and spectroscopic features of the cyclohexanone oxime molecule, highlighting the influence of different solvent environments on its behavior.